ANALISIS PENDAPATAN DAN TENAGA KERJA PADA SEKTOR PERTANIAN TERHADAP PERTUMBUHAN EKONOMI DI SUMATERA BARAT - Masdawia, Masdawia; Nengsih, Novia (AL-ITTIFAQ Jurnal Ekonomi Syariah, 2024)
This study aims to determine the influence of income and labor in the agricultural sector on economic growth in West Sumatra Province in 2008-2023. This research is a field research with a quantitative approach. This study uses secondary data on income and labor in the agricultural sector of West Sumatra from 2008-2023. Data collection techniques using documentation and Multiple Linear Regression Analysis techniques. The results of the study prove that income in the agricultural sector has a positive and significant effect on West Sumatra's economic growth in 2008 – 2023. Labor in the agricultural sector has a positive and significant effect on West Sumatra's economic growth in 2008-2023. Simultaneously, income and labor in the agricultural sector have a positive and significant effect on the economic growth of West Sumatra Province in 2008-2023. The R-Square value of 0.683 or 68.3 percent of the independent variables affected the dependent variables, while the rest were influenced by other variables that were not mentioned in this study.